The Effect Of Growth Mindset And Peer Social Support On Self-Regulated Learning - Rosito, Asina Christina; Pasaribu, Ronald Panaehan; Xtepia, Pia (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine 1) whether there is an influence of growth mindset on self-regulated learning among university students, 2) whether there is an influence of peer social support on self-regulated learning among university students, and 3) whether there is a combined influence of growth mindset and peer social support on self-regulated learning among university students. The participants of this study consisted of 138 university students from various universities in Medan. The research instruments used were the growth mindset scale, peer social support scale, and self-regulated learning scale. The data analysis technique employed was multiple regression analysis. The results of the study indicate the following: 1) there is no influence of growth mindset on self-regulated learning, 2) there is no influence of peer social support on self-regulated learning, and 3) there is no positive influence of growth mindset and peer social support on psychological well-being. A further discussion of these findings is presented in the discussion section.